PENATAAN KELEMBAGAAN KEPEGAWAIAN DALAM IMPLEMENTASI DESENTRALISASI MENUJU PROFESIONALISME PEGAWAI NEGERI - Wahyu Gia Uliantoro (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2008)
Decentralization requires professional human resources. As widely known, professional civil servants are very limited in numbers, particularly compared to the number of population to be served. Rightsizing policy is expected to be able to reduce the expectation gap. Furthermore, personnel institution should be restructured in accordance with the demand of decentralization bureaucracy.